Potential applications for antiviral therapy and prophylaxis in bovine medicine. (9th May 2014) - Newcomer, Benjamin W.; Walz, Paul H.; Givens, M. Daniel
Abstract: Viral disease is one of the major causes of financial loss and animal suffering in today's cattle industry. Increases in global commerce and average herd size, urbanization, vertical integration within the industry and alterations in global climate patterns have allowed the spread of pathogenic viruses, or the introduction of new viral species, into regions previously free of such pathogens, creating the potential for widespread morbidity and mortality in naïve cattle populations. Despite this, no antiviral products are currently commercially licensed for use in bovine medicine, although significant progress has been made in the development of antivirals for use against bovine viral diarrhea virus (BVDV), foot and mouth disease virus (FMDV) and bovine herpesvirus (BHV). BVDV is extensively studied as a model virus for human antiviral studies. Consequently, many compounds with efficacy have been identified and a few have been successfully used to prevent infection in vivo although commercial development is still lacking. FMDV is also the subject of extensive antiviral testing due to the importance of outbreak containment for maintenance of export markets. Thirdly, BHV presents an attractive target for antiviral development due to its worldwide presence. Antiviral studies for other bovine viral pathogens are largely limited to preliminary studies. This review summarizes the current state of knowledge of antiviral compounds against several key bovine pathogens and the potential for commercial antiviral applications in the prevention and control of several selected bovine diseases.